Beispiel Nr: 05
$ \text{Gegeben: } \\ p_1: y=a_1x^{2}+b_1x+c_1 \qquad p_2: y=a_2x^{2}+b_2x+c_2\\ \text{Gesucht:Schnittpunkte zwischen 2 Parabeln} \\ \text{Parabel-Parabel}\\ \textbf{Gegeben:} \\ p_1: y=-\frac{1}{2}x^2+x+2 \qquad p_2: y= \frac{1}{2}x^2-3x-3 \\ \\ \textbf{Rechnung:} \\f\left(x\right)=-\frac{1}{2}x^2+x+2\qquad g\left(x\right)= \frac{1}{2}x^2-3x-3\\ \bullet \text{Schnittpunkte zwischen zwei Funktionen} \\ f\left(x\right)=g\left(x\right) \\-\frac{1}{2}x^2+x+2= \frac{1}{2}x^2-3x-3 \\ -\frac{1}{2}x^2+x+2-( \frac{1}{2}x^2-3x-3)=0\\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ -1x^{2}+4x+5 =0 \\ x_{1/2}=\displaystyle\frac{-4 \pm\sqrt{4^{2}-4\cdot \left(-1\right) \cdot 5}}{2\cdot\left(-1\right)} \\ x_{1/2}=\displaystyle \frac{-4 \pm\sqrt{36}}{-2} \\ x_{1/2}=\displaystyle \frac{-4 \pm6}{-2} \\ x_{1}=\displaystyle \frac{-4 +6}{-2} \qquad x_{2}=\displaystyle \frac{-4 -6}{-2} \\ x_{1}=-1 \qquad x_{2}=5 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -1x^{2}+4x+5 =0 \qquad /:-1 \\ x^{2}-4x-5 =0 \\ x_{1/2}=\displaystyle -\frac{-4}{2}\pm\sqrt{\left(\frac{\left(-4\right)}{2}\right)^2- \left(-5\right)} \\ x_{1/2}=\displaystyle 2\pm\sqrt{9} \\ x_{1/2}=\displaystyle 2\pm3 \\ x_{1}=5 \qquad x_{2}=-1 \end{array}\\ \end{array}\\ \\ \text{Schnittpunkt }1\\ f(-1)=\frac{1}{2}\\ S(-1/\frac{1}{2})\\\\ \text{Schnittpunkt }2\\ f(5)=-5\frac{1}{2}\\ S(5/-5\frac{1}{2})\\$